Characteristic and Antimicrobial Resistance of Bacillus cereus Group Isolated from Food in Poland - Joanna Kowalska; Elżbieta Maćkiw; Dorota Korsak; Jacek Postupolski (Polish Journal of Food and Nutrition Sciences)
Bacillus cereus is a foodborne pathogen causing food safety issues due to the formation of difficult to eliminate spores and biofilms. The objective of this study was to investigate the occurrence of B. cereus (conducted as part of monitoring in 2017-2018) and the presence of a toxin gene in strains isolated from retail products (pastries/cakes; vegetables, spices, delicatessen products) in Poland, and to determine the susceptibility of these microorganisms to different antimicrobial agents. A total of 267 B. cereus isolates from food products were examined, of which 95.51% were found positive for the presence of at least one toxin gene, with the highest frequency of the nhe gene (91.39%). The hbl and cytK genes were detected in 53.56% and 44.19% of B. cereus strains, respectively. The lowest frequency was found for the ces gene (2.62%). The susceptibility of B. cereus isolates to 16 antimicrobials was investigated. Ampicillin and penicillin resistance was the most common resistance phenotype and was identified in 100% of the B. cereus isolates. In addition, the tested isolates exhibited resistance to: amoxicillin-clavulanic acid (96.25%), cephalothin (67.79%), ceftriaxone (64.42%), rifampicin (46.82%), trimethoprim-sulfamethoxazole (5.62%), quinupristin/dalfopristin (4.87%), chloramphenicol (3.75%), clindamycin (2.62%), teicoplanin (1.87%), erythromycin (1.87%), ciprofloxacin (0.75%), imipenem (0.75%), tetracycline (0.37%), and gentamicin (0.37%). The study results contribute to characterizing the diversity of B. cereus isolated from various food products in Poland and their impact on food safety and public health. This study delivers practical information on antibiotic resistance and the frequency of toxin genes among strains isolated from food.